Targeted intracellular delivery of dimeric STINGa by two pHLIP peptides for treatment of solid tumors - Moshnikova, Anna; DuPont, Michael; Iraca, Marissa; Klumpp, Craig; Visca, Hannah; Allababidi, Dana; Pelzer, Phoebe; Engelman, Donald M.; Andreev, Oleg A.; Reshetnyak, Yana K. (Frontiers in Pharmacology, 2024)
We have developed a delivery approach that uses two pHLIP peptides that collaborate in the targeted intracellular delivery of a single payload, dimeric STINGa (dMSA). dMSA was conjugated with two pHLIP peptides via S-S cleavable self-immolating linkers to form 2pHLIP-dMSA. Biophysical studies were carried out to confirm pH-triggered interactions of the 2pHLIP-dMSA with membrane lipid bilayers. The kinetics of linker self-immolation and dMSA release, the pharmacokinetics, the binding to plasma proteins, the stability of the agent in plasma, the targeting and resulting cytokine activation in tumors, and the biodistribution of the construct was investigated. This is the first study demonstrating that combining the energy of the membrane-associated folding of two pHLIPs can be utilized to enhance the targeted intracellular delivery of large therapeutic cargo payloads. Linking two pHLIPs to the cargo extends blood half-life, and targeted delivery of dimeric STINGa induces tumor eradication and the development of robust anti-cancer immunity.